PROFIL KETERAMPILAN GERAK DASAR SISWA SD NEGERI 35 PADANG SARAI - Maharani, Lintang; Andli Marta, Ibnu; Syahrial Bakhtiar; Risky Syahputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the fundamental motor skills of elementary school students at SD Negeri 35 Padang Sarai. The focus of the research is on fundamental motor abilities, including locomotor skills and object control skills, which are essential components of motor development in school-aged children. A quantitative approach with a descriptive design was employed. The population consisted of 369 students of SD Negeri 35 Padang Sarai, while the sample comprised 53 third-grade students selected through cluster sampling based on existing class groups. Data were collected using the Test of Gross Motor Development-2 (TGMD-2), which assesses both locomotor and object control skills. The data were analyzed using descriptive percentage statistics and a five-scale classification formula to determine students’ fundamental motor skill levels. The findings revealed that the overall fundamental motor skills of the students were categorized as moderate, with a total score of 73. Locomotor skills obtained a score of 36, classified as moderate, while object control skills also scored 36, falling into the same category. These results indicate that students’ fundamental motor skills remain at a medium level, suggesting the need for more structured Physical Education programs to optimize motor development among elementary school students.